Successful Treatment of Iron-Overload Cardiomyopathy in Hereditary Hemochromatosis With Deferoxamine and Deferiprone - Tauchenová, Lydie; Křížová, Barbora; Kubánek, Miloš; Fraňková, Soňa; Melenovský, Vojtěch; Tintěra, Jaroslav; Kautznerová, Dana; Malušková, Jana; Jirsa, Milan; Kautzner, Josef (The Canadian journal of cardiology, 2016)
There is scarce evidence regarding the use of iron chelators in patients with hereditary hemochromatosis who are intolerant of phlebotomy or erythrocytapheresis. A 52-year-old man with genetically confirmed HFE hemochromatosis presented with liver disease and heart failure with severe left ventricular systolic dysfunction. Because of anemia after initial treatment, we added intravenous deferoxamine followed by oral deferiprone to less frequent erythrocytapheresis, which normalized systolic function within 1 year. Repeated cardiac magnetic resonance imaging revealed improvement of the T2* relaxation time. This report illustrates the beneficial effect of iron chelators in individuals with HFE hemochromatosis and poor tolerance of erythrocytapheresis.
Keywords: tepový objem; Hemochromatosis Protein; chelátory železa; Iron Overload; magnetická rezonance kinematografická; transferin; Humans; Heart Failure; Stroke Volume; srdeční selhání; lidé středního věku; Transferrin; Deferiprone; Hemochromatosis; Pyridones; deferipron; Liver Diseases; Iron Chelating Agents; Ferritins; ferritiny; výsledek terapie; lidé; nemoci jater; stupeň závažnosti nemoci; Magnetic Resonance Imaging, Cine; Male; Middle Aged; deferoxamin; Treatment Outcome; hemochromatóza; dysfunkce levé srdeční komory; protein hemochromatózy; pyridony; Deferoxamine; Cardiomyopathies; Severity of Illness Index; Ventricular Dysfunction, Left; přetížení železem; mužské pohlaví; kardiomyopatie